Analisis Resiko Pasar Saham Berdasarkan Value at Risk Pada Perusahaan Telekomunikasi yang Tercatat di Bei - Desi Rapang; Benyamin Mongan; Johannes Baptista Halik (Yos Soedarso Economic Journal (YEJ), 2024)
This research analyzes stock market risk based on Value at Risk (VaR) for telecommunications companies listed on the Indonesia Stock Exchange (IDX). The study focuses on PT Telkom Tbk (TLKM), PT Indosat Tbk (ISAT), PT Smartfren Tbk (FREN), and PT EXCL Tbk (AXIATA). The data used consists of daily stock prices from 2021 to 2023. Risk measurement is conducted using the Variance-Covariance method, a parametric approach to calculating VaR. The study also employs the Kolmogorov-Smirnov test to statistically determine if the data is normally distributed. Among the 36 months of return data, ISAT's mean return is higher than the other three stocks, indicating a greater expected investment return. In terms of risk, the standard deviation is lowest for TLKM's stock, suggesting that TLKM's return volatility is lower compared to the other three stocks.